(untitled) (Jurnal Bahasa, 2009)
Malay derivatives with affix -an /-an/ have three patterns of articulation in the final syllable, i.e. (i) consonant + /-an/, (ii) single vowel + /-an/, and (iii) diphthong + /-an/. The third pattern of the final syllable that makes a vowel cluster with /-an/ produces an acoustic effect that is clearly different from that in the second pattern in which a glide (transitional) sound appears in the vowel cluster as in [-i+ja+an] or [-u+wa+an]. However, the specific feature found in the polarized vowel cluster (iii) seems to receive little attention in phonetic studies, so that categorization of polar (it) and (iii) is often made to fall into one vocal cluster structure, i. e. -VcVC#. This article aims at examining the structure of the glide in a vowel cluster using an experimental phonetics method. The phonetic data for this experiment were collected from 30 native speakers of Malay.